The Economic Efficiency as a Main Factor in The Development of Enterprises - Dominika KRÓL-SMETAK; Ireneusz MICIUŁA; Karolina ROGOWSKA (Communications of International Proceedings, 2022)
The aim of the article is to define the essence and dependence of enterprise development on economic efficiency. Enterprises operating in the conditions of increasing environmental volatility, increasing uncertainty and risk must look for ways that will enable them to develop in a competitive market and achieve success. Therefore, enterprises are forced to search for the best ways, techniques and methods to increase their effectiveness. Nowadays, the basis for the success of companies is access to information and knowledge as well as the appropriate use of intellectual capital and cost optimization, which affects the economic efficiency of the organization in its entirety. The article indicates practical elements and strategies that directly translate into the functioning of enterprises, which allows us to understand their functioning and their impact on the entire economy. A company operating in the conditions of the 21st century must be effective, learning, flexible and able to adapt to changes, because this determines its competitiveness and efficiency, which is the main measure of the company's operation.
Keywords: Economic Efficiency; Economic Development; Economy; Entrepreneurship; Management; Business.